Why Christian Schools Should Adopt Restorative Justice? - Samuel Dwioktorianto Effendy (Diligentia: Journal of Theology and Christian Education, 2020)
Christian schools have the responsibility to teach students to view everything from God’s perspective. Hence, all components of Christian education, including discipline practices, should be based on the Bible. Traditionally, the discipline approach in schools is mainly retributive justice that focuses on the rules that are broken, the offenders and the punishments. The offenders should get the deserved punishment for breaking the rules. A different approach, that is restorative justice, focuses on addressing the harm caused, the victims’ feeling and restoring the broken relationship caused by the offense through reconciliation. To find the most biblical approach to be implemented in Christian schools, this paper first looks at the presupposition of both approaches through literature studies and then review it in the light of the Word of God. The result is apparent that restorative justice should be adopted by Christian schools in order to stay faithful to the mandate which is to bring students to God. Further arguments on the importance of adopting this approach are presented concisely. Nevertheless, more research is needed in this area to ensure successful implementation.